2007
DOI: 10.1001/archfaci.9.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase and Restylane

Abstract: trum of the impact of the incision from disfiguring (1) to imperceptible (10). The reviewers felt that the incision obtained 94% imperceptibility.Comment. Conchal cartilage is widely accepted for use during revision and reconstructive rhinoplasty, orbital wall reconstruction, and eyelid repair. The anterior approach to conchal cartilage harvest has become the most popular technique. After observing successful changes in the ear for anterior conchal cartilage harvest, some authors 10,11 have even developed new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
(1 reference statement)
0
11
0
3
Order By: Relevance
“…Popkin also described similar success using the identical method in scleroderma patients with chronic, nonhealing ankle ulcers 31 . In 2007, Soparkar and Patrinely reported using hyaluronidase at 75 to 300 U in patients' legs to treat acute pretibial myxedema associated with autoimmune thyroid disease 24 …”
Section: Hyaluronidase In Dermatology (All Off‐label Uses)mentioning
confidence: 97%
See 3 more Smart Citations
“…Popkin also described similar success using the identical method in scleroderma patients with chronic, nonhealing ankle ulcers 31 . In 2007, Soparkar and Patrinely reported using hyaluronidase at 75 to 300 U in patients' legs to treat acute pretibial myxedema associated with autoimmune thyroid disease 24 …”
Section: Hyaluronidase In Dermatology (All Off‐label Uses)mentioning
confidence: 97%
“…There is the worry that high hyaluronidase concentrations can dissolve the native HA, with resulting cosmetic deformity 23 . In 2005, Soparkar and colleagues described using 375 U of hyaluronidase to dissolve HA filler in one patient's face over 10 days without any discernable change in native facial volume 24 . They reported that they routinely use 150 to 200 U of hyaluronidase for every milliliter of HA they wish to remove 23 .…”
Section: Hyaluronidase In Dermatology (All Off‐label Uses)mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to expect a good postoperative outcome an interdisciplinary approach to esthetic treatment planning and treatment execution is a primary concern. * [20][21][22][23] The product is approved by the Federal Food and Drug Administration (FDA). 19 Recently a gel of hyaluronic acid generated by Streptococcus species of bacteria, chemically cross-linked with butanediol diglycidyl ether (BDDE), and stabilized and suspended in phosphate buffered saline at pH 7 and concentration of 20 mg/mL and fee of animal protein has been successfully used to reduce or eliminate facial creases and various other abnormalities.…”
Section: Introductionmentioning
confidence: 99%